Respuesta :

Since 2x,2x does not contain the variable to solve for, move it to the right side of the equation by subtracting 2x,2x from both sides.−y=−2x+9-y=-2x+9Multiply each one −y=−2x+9-y=-2x+9 by −1-1Multiply each one in −y=−2x+9-y=-2x+9 by −1-1.−y−1=−2x−1+9⋅−1-y-1=-2x-1+9⋅-1make it simple −y−1-y-1.Multiply some more. −1-1 by −1-1 to get 11.1y=−2x−1+9⋅−11y=-2x-1+9⋅-1Multiply yy by 11 to get yy.(but Y?)y=−2x−1+9⋅−1y=-2x-1+9⋅-1Simplify each stuff that you simplify. Multiply...again..... −1-1 by −2-2 to get 22.y=2x+9⋅−1y=2x+9⋅-1Multiply some more..... 99 by −1-1 to get −9-9.y=2x9.
Slope intercept is written as y=mx+b. So step one would be to add y to both sides of the equation and you get

2x-y+y = 9+y..the y's cancel out so it would be 2x = 9 +y

Now subtract 9 from both sides of the equation and you have 2x-9=9-9+y  in that 9-9 = 0 you now have 2x- 9 = y or  y= 2x-9.

2x-9 = y